Development of the Adolescent Cancer Suffering Scale - Christelle Khadra; Sylvie Le May; Isabelle Tremblay; France Dupuis; Chantal Cara; Geneviève Mercier; Marie France Vachon; Jacinthe Lachance Fiola (Pain Research and Management)
BACKGROUND: While mortality due to pediatric cancer has decreased, suffering has increased due to complex and lengthy treatments. Cancer in adolescence has repercussions on personal and physical development. Although suffering can impede recovery, there is no validated scale in French or English to measure suffering in adolescents with cancer.